2003
DOI: 10.1590/s0034-89102003000500016
|View full text |Cite
|
Sign up to set email alerts
|

Ecologia de Lutzomyia (Nyssomyia) whitmani em área urbana do município de Maringá, Paraná

Abstract: ObjectivesTo study the fauna, hours of activity and seasonality of phlebotomines in forest animal habitats in the Ingá Park, on the urban perimeter of the municipality of Maringá, Paraná State, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
2
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 14 publications
(24 reference statements)
3
20
2
13
Order By: Relevance
“…For Ny. whitmani captured using the white trap, there were two peaks for the females and the last peak was at a time close to that found in Maringá, PR (12:00 am-01:00 am) (Teodoro et al 2003), but differed from that in Bandeirantes (08:00 pm-10:00 pm) (Massafera et al 2005) and in the municipality of Corguinho, MS (06:00 pm-07:00 pm) (Galati et al 1996). Although seasonality studies of sandflies are still needed, the results obtained in this present study suggest that the spring and summer are the seasons of greatest risk of human infection by Leishmania.…”
Section: Discussionsupporting
confidence: 70%
“…For Ny. whitmani captured using the white trap, there were two peaks for the females and the last peak was at a time close to that found in Maringá, PR (12:00 am-01:00 am) (Teodoro et al 2003), but differed from that in Bandeirantes (08:00 pm-10:00 pm) (Massafera et al 2005) and in the municipality of Corguinho, MS (06:00 pm-07:00 pm) (Galati et al 1996). Although seasonality studies of sandflies are still needed, the results obtained in this present study suggest that the spring and summer are the seasons of greatest risk of human infection by Leishmania.…”
Section: Discussionsupporting
confidence: 70%
“…The highest rainfall was recorded in September and October, although the MHCs in these months were low. Although larger collections of sand fl ies were recorded in the warmer and humid months in Paraná (Massafera et al 2005, Reinhold-Castro et al 2008, Teodoro et al 2003a, we found no correlation between temperature or rainfall and the number of insects collected in our study. Generally, wind, low temperatures and rainfall affect the activity of sand fl ies, thereby reducing their population density (Aguiar et al 1985, Mayo et al 1998, Teodoro et al 2003a, Saraiva et al 2006.…”
Section: Discussioncontrasting
confidence: 84%
“…whitmani in Rio Verde de Mato Grosso showed a higher density in drier periods (fall and winter) (Fig. 1), as occurred in the Bodoquena and Corguinho municipalities, both in Mato Grosso do Sul state (Galati et al 1996;Galati et al 2003), and Maringá, in Paraná state (Teodoro et al 2003). Fig.…”
Section: Resultsmentioning
confidence: 82%